Wisdom Myth and Mythology: An Essay in Understanding a Theological Tradition - Mack, Burton L. 1931-2022 (1970)
The burning question of theodicy, raised by the cruel realities of the exile and its aftermath, drove the wisdom schools to creative theological work. By using the graphic language of wisdom mythology, the affirmation of Yahweh's lordship over the entire order of creation is made in such a way that the exile can now be seen to demand faith rather than resignation.